Analysis of female salivary gland proteins of the Anopheles barbirostris complex (Diptera: Culicidae) in Thailand - Narissara Jariyapan (2018)
Electrophoretic protein profiles of female salivary glands of five sibling species within the Anopheles barbirostris complex, namely A. barbirostris species A1 (Forms A, B, and D), A2, A3, and A4 and Anopheles campestris-like (Forms B and E), were analyzed. At least eight major and several minor protein bands were detected in the glands of each species, of which each morphological region contained different major proteins. The protein profiles distinguished the five sibling species. The variability in major proteins among species was observed in the 40-48, 32-37, and 10-18 kDa ranges. No difference in protein profiles was found in different cytogenetic forms. Polymorphism of the protein profiles within species was only noted in species A4. The lowest major protein (marker) band of each species showed remarkably different relative mobility on SDS-polyacrylamide gels. NanoLC-MS analysis revealed that the marker protein of some species matched with a protein involving in blood feeding, gSG6, of Anopheles gambiae and Anopheles freeborni. These results might be useful for construction of an additional tool to distinguish the five sibling species and lead to further study on the evolution of blood feeding and pathogen transmission. © 2010 Springer-Verlag.